2005
DOI: 10.4049/jimmunol.175.7.4301
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Inhibition of CD1d1-Mediated Antigen Presentation: Reciprocal Regulation by p38 and ERK

Abstract: A critical component of the host’s innate immune response involves lipid Ag presentation by CD1d molecules to NK T cells. In this study we used murine CD1d1-transfected L (L-CD1) cells to study the effect of viruses on CD1d-mediated Ag presentation to NKT cells and found that an infection with vesicular stomatitis and vaccinia (but not lymphocytic choriomeningitis) virus inhibited murine CD1d1-mediated Ag presentation. This was under the reciprocal control of the MAPKs, p38 and ERK, and was due to changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
99
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 69 publications
(114 citation statements)
references
References 49 publications
13
99
1
1
Order By: Relevance
“…The cells were then washed with phosphate-buffered saline (PBS), fixed in 0Á05% paraformaldehyde and co-cultured with the indicated NKT cell hybridomas as described previously. 23 To examine the ability of a-GalCer to rescue the drug-induced reduction in CD1d-mediated antigen presentation, camptothecin-treated or untreated LMTK-CD1d1 cells were treated with DMSO or a-GalCer (100 ng/ml) for 1 hr. The cells were then extensively washed, fixed and co-cultured with NKT cell hybridomas as above.…”
Section: Generation Of Bone Marrow-derived Dendritic Cells (Bmdc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were then washed with phosphate-buffered saline (PBS), fixed in 0Á05% paraformaldehyde and co-cultured with the indicated NKT cell hybridomas as described previously. 23 To examine the ability of a-GalCer to rescue the drug-induced reduction in CD1d-mediated antigen presentation, camptothecin-treated or untreated LMTK-CD1d1 cells were treated with DMSO or a-GalCer (100 ng/ml) for 1 hr. The cells were then extensively washed, fixed and co-cultured with NKT cell hybridomas as above.…”
Section: Generation Of Bone Marrow-derived Dendritic Cells (Bmdc)mentioning
confidence: 99%
“…22 Therefore, CD1d-dependent NKT cell activation bridges the innate and adaptive immune responses. 22 We found that signal transduction pathways [both MAPK and protein kinase Cd (PKCd)] regulate CD1d-mediated antigen presentation, 23,24 and they are also crucial players in the induction of apoptosis. 19,25 Thus, the present study investigated the effect of apoptosis generation on CD1d-mediated antigen presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such a model could explain the recent observation that viral pathogens, including HSV1, have evolved mechanisms to subvert CD1d antigen presentation [28][29][30][31][32][33]. Future studies will reveal more insight into the intriguing interplay between viruses and the CD1 antigen presentation system and the ligands recognized by NKT cells in the context of virus infection.…”
Section: Discussionmentioning
confidence: 97%
“…Intriguingly, in mouse models therapeutic activation of NKT cells by aGalCer helps to clear virus [18,25] or improves disease outcome [12,26]. Moreover, viruses subvert antigen presentation through CD1d [27][28][29][30][31][32][33], indicating its importance in antiviral immune defense.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation